The impact of social media use on tolerance, community peace, online ethical awareness among adolescents in the United Arab Emirates - Al Ketbi, Najia; Habes, Mohammed; Shaheen, Lubna; Attar, Razaz Waheeb; Tahat, Dina; Alhazmi, Amal Hassan (Frontiers in Psychology, 2025)
Social media use has increased after the COVID-19, indicating several effects on users. Talking specifically about its effects on adolescents, several studies have witnessed its positive and negative consequences on young users. This research also aims to examine the positive effects of social media use on adolescents from a Media Mindfulness Perspective, including tolerance, community peace, and online ethical awareness. Theoretically supported by Social Learning Theory, the data were gathered using 379 structured questionnaires. Results indicated an overall positive influence of social media use on adolescents in UAE. It is found that social media use positively affects tolerance among adolescents, suggesting an improved tolerance among the relevant users. Also, the effect of social media uses on community peace remained positive, implying that digital platforms are constructive means of teaching peace and harmony. Finally, results also indicated the positive effects of social media use on online ethical awareness among adolescents in UAE. Overall, these results suggest a positive, constructive role of social media use in changing the behaviors of the young generation. Under the social learning theory, this study also suggested social media as a powerful tool for learning positive behaviors, further influencing and improving societal peace and harmony. Finally, the study’s significance and limitations are discussed.